Planes, trains and automobiles [videorecording (Blu-Ray)] / Paramount pictures presents ; a John Hughes film. - Martin, Steve, 1945-; Candy, John; Hughes, John, 1950-2009; Hughes, John, 1950-2009; Hughes, John, 1950-2009 (Paramount Home Entertainment, 2012)
An uptight businessman faces disaster after disaster as he tries to get back home in time for his family's Thanksgiving dinner. Along the way he is joined by an obnoxious yet lovable salesman that will not leave him alone. Includes featurettes and deleted scene.